Ongoing speciation within the Anastrepha fraterculus cryptic species complex: the case of the Andean morphotype - Devescovi, Francisco; Abraham, Solana; Roriz, Alzira K.P.; Nolazco, Norma; Castañeda, Rosario; Tadeo, Eduardo; Caceres, Carlos; Segura, Diego Fernando; Vera, María Teresa; Joachim-Bravo, Iara; Canal, Nelson; Rull Gabayet, Juan Antonio (Wiley, 2019)
The Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) cryptic species complex is currently composed of seven taxonomically recognized morphotypes. Both, pre‐ and post‐zygotic isolation has been documented among four of these morphotypes, revealing that in fact they appear to be distinct biological entities. In order to progress in the full delimitation of species within the complex, we examined reproductive isolation between a Colombian population of the Andean morphotype and populations belonging to four other morphotypes spanning from Mexico to Argentina. Flies from the Andean morphotype exhibited strong pre‐zygotic mating isolation through temporal partitioning of mating activity. Post‐zygotic isolation was observed for crosses of males of all morphotypes and Andean morphotype females, yet most of the F1 hybrid ♂ × F1 hybrid ♀ self‐crosses showed normal levels of fertility, a finding suggesting a nuclear–cytoplasmic interaction according to previous studies. Overall, the Andean morphotype within the complex also appears to be a distinct biological entity. We discuss the implications of these findings for the understanding of speciation mechanisms in the Neotropical genus Anastrepha.